A state‐space model to estimate spawning rates in a Ruditapes philippinarum population. Issue 2 (3rd January 2023) - Hanyu, Kazuhiro
Abstract: The Ruditapes philippinarum catch in Japan has drastically declined and its recovery is a major challenge. The spawning rates and egg output need to be estimated to discuss stock management strategies. However, it is difficult to observe these directly in a field survey. This study proposes a state‐space model to estimate spawning rates in an R. philippinarum population using the number of individuals at each developmental stage based on traditional histological observations of the gonads. An example of its application to monthly observed data of an R. philippinarum population on the western Japanese coast is also presented. The spawning seasons were quantitatively detected in spring and fall, and the durations were estimated to be 2.8 months in spring and 3.0–3.5 months in fall, based on the spawning rates. The mean condition factor was lower in fall than in spring, but females with a high condition factor were also found in fall. The egg output of these individuals during the fall may be large. The spawning frequency per individual was estimated to be 6.5 times per year based on the model, indicating that R. philippinarum is an r‐strategy species capable of multiple spawning. Questioning how the spawning rates vary with individual size/age and environmental conditions is essential for estimating egg output in R. philippinarum populations. The state‐space model in this study can contribute to the quantification of spawning rates. The results will contribute to estimating the egg output and stock management strategies. Abstract : This study proposed a state‐space model to estimate spawning rates in an Ruditapes philippinarum population using the number of individuals at each developmental stage based on traditional histological observations of the gonads. An example of its application to monthly observed data of an R. philippinarum population on the western Japanese coast is also presented.